Molecular Cloning, Nucleotide Sequencing, and Characterization of a 27-kDa Antigenic Protein from Paracoccidioides brasiliensis (1996)
ABSTRACT: A gene encoding a 27-kDa antigenic protein fromParacoccidioides brasiliensiswas cloned, sequenced, and characterized. A cDNA library of the mycelial phase was produced and packed in Uni-Zap-XR vector, λ Zap II synthesis kit (Stratagene, La Jolla, CA). The screening of the library was carried out using a pool of sera from paracoccidioidomycosis patients that had proven reactive in serological testing. Among 44,000 immunoscreened clones from the library, 2 were positive (clones 2 and 3). The former was not characterized further. The latter has a 1-kb DNA insert with an open reading frame encoding a protein of 259 amino acids with a predicted molecular mass of 28.6 kDa (27 kDa by SDS–PAGE). This protein corresponds to a 25-kDa protein in antigenic preparations ofP. brasiliensisas determined by Western blot analysis. Comparison of the transcribed sequence with different gene banks failed to reveal a high degree of homology with other proteins. The cloned DNA fragment was easily expressed inEscherichia coliwithout the need of induction by isopropyl-β-D-thiogalactopyranoside. These findings suggest that the gene encodes aP. brasiliensis-specific protein.